Strategies, models and biomarkers in experimental non-alcoholic fatty liver disease research. (July 2015) - Willebrords, Joost; Pereira, Isabel Veloso Alves; Maes, Michaël; Crespo Yanguas, Sara; Colle, Isabelle; Van Den Bossche, Bert; Da Silva, Tereza Cristina; de Oliveira, Cláudia Pinto Marques Souza; Andraus, Wellington; Alves, Venâncio Avancini; Cogliati, Bruno; Vinken, Mathieu
Abstract: Non-alcoholic fatty liver disease encompasses a spectrum of liver diseases, including simple steatosis, steatohepatitis, liver fibrosis and cirrhosis and hepatocellular carcinoma. Non-alcoholic fatty liver disease is currently the most dominant chronic liver disease in Western countries due to the fact that hepatic steatosis is associated with insulin resistance, type 2 diabetes mellitus, obesity, metabolic syndrome and drug-induced injury. A variety of chemicals, mainly drugs, and diets is known to cause hepatic steatosis in humans and rodents. Experimental non-alcoholic fatty liver disease models rely on the application of a diet or the administration of drugs to laboratory animals or the exposure of hepatic cell lines to these drugs. More recently, genetically modified rodents or zebrafish have been introduced as non-alcoholic fatty liver disease models. Considerable interest now lies in the discovery and development of novel non-invasive biomarkers of non-alcoholic fatty liver disease, with specific focus on hepatic steatosis. Experimental diagnostic biomarkers of non-alcoholic fatty liver disease, such as (epi)genetic parameters and '-omics'-based read-outs are still in their infancy, but show great promise. In this paper, the array of tools and models for the study of liver steatosis is discussed. Furthermore, the current state-of-art regarding experimental biomarkers such as epigenetic, genetic, transcriptomic, proteomic and metabonomic biomarkers will be reviewed.